Sh*t my dad says [compact disc, unabridged] - Halpern, Justin, 1980- (Harper Audio, 2010)
Tuesdays with Morrie meets F My Life in this hilarious coming-of-age book about a son's relationship with his foul-mouthed father by the 29-year-old comedy writer who created the massively popular Twitter feed of the same name.